Delayed cord clamping versus intact umbilical cord-milking and its effects on maternal blood loss: a randomised controlled trial - Meghana, Kanchibhotla; Bellad, Mrutyunjaya B.; Kumar, Chakrala R.; Koppad, Bhavana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The ideal timing of cord clamping has been controversial and debated over decades. Delayed cord clamping has many advantages owing to enhanced placental transfusion on neonates but provides limited evidence on maternal postpartum blood loss. The objective of the study was to estimate the maternal blood loss after delayed cord clamping versus umbilical cord milking. Methods: A randomized controlled trial was conducted in KLE’s Dr. Prabhakar Kore Hospital, at Belagavi district in Karnataka over 18 months. In the delayed cord clamping (group A- DCC) group, the cord was clamped 60 seconds after the delivery of a newborn. In the intact umbilical cord milking (group B- UCM) group, cord blood was milked 5-8 times for 15-20 seconds towards the neonate. The primary outcome of the study was to estimate the maternal blood loss by comparing the change in hemoglobin and hematocrit values before and after delivery. Furthermore, neonatal outcome was assessed by comparing serum ferritin at third month of life. Results: Maternal blood loss was estimated by a drop in post-delivery hemoglobin, showed a significant difference between the two groups (group A-DCC group=1.76±0.1 gm% and group B-UCM group=1.73±0.1 gm%; p<0.001). Additional administration of uterotonics for medical management of the cases also showed a significant difference (p=0.049) with higher usage among the DCC group. Conclusions: From the present study, it was observed that umbilical cord milking was equally effective and time-saving with the advantages of delayed cord clamping with reduced estimated maternal blood loss.